Escolas do campo e formação territorial dos assentamentos de reforma agrária do município de Cruz do Espírito Santo-PB - Nogueira, Alexandre Peixoto Faria (2010)
Addressing the agrarian question as a historical process in the formation of Brazilian space puts us facing several possibilities for analysis. For example, we can investigate the processes of agrarian concentration, the action of agribusiness, the role of rural social movements, the regulations of the land laws, and other subjects. In this research we analyze the historical absence of policies for education and for rural areas setting the following questions: To what extent the relationship between education, agrarian reform and territorial training helps us to understand the uniqueness of the national land question? Does this tripod ensures the social reproduction of families settled? To answer these questions, we started the study of the role of the Rural Schools in the formation of local land reform settlements in the municipality of Cruz do Espírito Santo, in the Zona da Mata, state of Paraíba. In this study, the school in the rural areas is considered as a new achievement of the organization and struggle of rural households in favor of strengthening these areas of agrarian reform in its development and its social reproduction. First we present a discussion on the paradigm of Countryside Education, questioning if it can be regarded as a strengthening of a policy of agrarian reform. Then we analyze critically the policies of agrarian reform during the various Brazilian governments emphasizing the treatment of education in rural areas had at one time. Finally, we tried to understand the State and its class character, especially in the development model adopted for the countryside, whether in land reform or in the education in rural areas.